Problematyka przejęcia w trybie art. 98 ustawy o gospodarce nieruchomościami gruntu oddanego w użytkowanie wieczyste w kontekście zakazu wywłaszczania nieruchomości stanowiących własność Skarbu Państwa - Kruś, Maciej; Zańko, Katarzyna (Studia Prawa Publicznego, 2022)
The article offers a detailed interpretation of Art. 98 sec. 1 of the Act of August 21, 1997 on Real Estate Management (r.e.m.) in order to answer the question of what effect in terms of the ownership of the State Treasury is related to the ﬁnal division decision issued in relation to plots of land designated for public-municipal roads at the request of the perpetual usufructuary of the property. The authors of the article support such an interpretation of Art. 98 sec. 1 r.e.m. that takes into account the broader legal context of this regulation and enables effective equipping of relevant entities – communes in this case – with real estate allowing for the construction of public-communal roads on them. This entails the necessity to transfer ex lege the ownership of the separated plot of land from the State Treasury to the appropriate commune as a result of an application submitted by the perpetual usufructuary. The authors’ conclusions are based on a linguistic, comparative, teleological and historical interpretation, taking into account the 2000 amendment to the provision. For comparison purposes, the content of Art. 105 paragraph. 4 of this Act is taken into account. The article also considers the relation of the institution discussed here to the regulations concerning expropriation. This applies to the prohibition of the expropriation of real estate owned by the State Treasury under Art. 113 sec. 2 r.e.m., in the narrow, formal meaning of this concept resulting from its deﬁnition in Art. 112 sec. 2 r.e.m. The discussion also includes expropriation in a broad, material sense resulting from Art. 21 sec. 2 of the Constitution of the Republic of Poland. In both cases, the analysis leads to the conclusion that depriving the State Treasury of its property for the beneﬁt of the commune in the case in question does not constitute expropriation, but is an example of communalisation, which is an acceptable form of equipping the commune with public property.